Influenza to Follow COVID-19 Wave: the facts and flaws of influenza in Pakistan - Khan, Shahzaib Muhammad; Saleem, Ali Faisal (Infectious Diseases Journal of Pakistan, 2022)
Pneumonia is the leading cause of mortality for children less than 5 years old in Pakistan. Respiratory viruses such as Influenza, Parainfluenza and Respiratory syncytial virus (RSV) remain the most common etiology of infection amongst hospitalized patients with community acquired pneumonia.CDC estimates for the pre-pandemic 2019-2020 influenza season disease burden was as high as 66.2 cases per 100,000 individuals with a test positivity rate of 16.8%. Global assessment of disease burden showed 19% test positivity rate from respiratory samples collected between November and December 2019.